Direct growth and post-treatment of zeolitic imidazolate framework-67 on carbon paper: an effective and stable electrode system for electrocatalytic reactions. Issue 39 (21st September 2022) - Nguyen, Anh Ngoc; Tran, Ngoc Minh; Yoo, Hyojong
Abstract : Co-based MOFs are directly grown using an electrodeposited layer of Co(OH)2 on carbon paper and converted to cobalt sulfide (Co x S y ) through a post-treatment process. The final electrode system exhibits remarkable oxygen evolution reaction performance. Abstract : Metal–organic framework (MOF)-derived transition metal chalcogenide (TMC) materials have been increasingly utilized owing to their superior electrocatalytic activity and durability. To prevent any limitations in the immobilization of nanocatalysts onto a working electrode substrate with binders, direct growth of MOF-derived TMC catalysts on a conductive substrate could be an improved fabrication strategy for realizing durable electrode systems. Herein, we report a facile method for growing cobalt-based zeolitic imidazolate framework-67 (ZIF-67) by using a cobalt hydroxide (Co(OH)2 ) layer electrodeposited on carbon paper (CP). Subsequently, ZIF-67 was used as a sacrificial template and converted into amorphous cobalt sulfide (Co x S y ) to form Co x S y @Co(OH)2 /CP by a post-treatment process (etching with thioacetamide). The final CP electrode incorporating the catalytic system (Co x S y @Co(OH)2 /CP) exhibited remarkable oxygen evolution reaction (OER) performance with an overpotential of 180 mV at 10 mA cm −2 and stable activity after 24 h of continuous operation at a high current density of 50 mA cm −2 . The excellent OER activity of the fabricated electrode system is attributed to the high surface area inherited from the MOF template, the robust structure of the catalytic system, the relatively large number of unsaturated surface sites of Co x S y, and the heterogeneous interface of amorphous Co x S y –crystalline Co(OH)2 .